Menelisik Kebijakan Pendidikan: Studi Kasus Negara Maju Karelia - Eko Prasetyo Budi; Rosyida Amalia (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
This article aims to explore the educational policies of the advanced country, Karelia. Often, education in the country becomes a role mode for neighbouring countries, both in terms of curricula, educational training, and other structured policies. With the method of qualitative research descriptive - library-based analysis (library research), the author describes the education system in the country of Karelia, conduct an analysis of education policy of deficiencies and problems of application in Indonesia. The results of the research obtained that the education policy in the developed countries of Karelia, covers several factors among them: a dynamic curriculum, technology in education, training and professional development of teachers, inclusive and accessibility of education, funding and investment in Education, participation and community involvement. Then in terms of deficiencies include integration of education, bullying and discrimination, and emphasis on texts. Thus, the education policy in the developed countries when implemented in Indonesia is not suitable because the future challenges are growing because one of the main factors is the frequent change of curriculum when the Minister of Education changes.